Corporate governance determinants in emerging markets: evidence from Brazil - Leão, A.; Da Silva Montezano, R. M.; Lameira, V. D. J.; Amaral-Baptista, M.; Harris, J. E. (International Journal of Industrial and Systems Engineering, 2016)
We studied the possible determinants of the adoption of good corporate governance practices by Brazilian firms listed on the São Paulo Stock Exchange between 2003 and 2008, in accordance with Durnev and Kim (2005). Durnev and Kim demonstrated that three firm-level factors may influence the quality of corporate governance practices in countries with low legal protection: growth opportunities, external financing needs and ownership concentration. We operationalised these factors as independent variables that may be related to the quality of corporate governance practices. The firm level of corporate governance was measured by an index comprising a set of good governance prescriptions. We addressed the limitations of endogeneity and reversal causality employing multiple regressions and structural equations modelling. Results revealed that firm-level corporate governance is positively related to growth opportunities and external financing needs, and negatively related to ownership structure confirming the Durnev and Kim's hypotheses.